Improvement on the quality assurance system in higher education (Eurasian Scientific Herald, 2023)
This paper identifies and clarifies the fundamental concepts and implementation frameworks of Quality Assurance and Total Quality Management in Higher Education (sometimes also known as Total Quality Education). It is based on research, empirical studies, best practices and consultancy activities. The paper is useful both for quality professionals as well as academicians in interpreting the critical issues and designing the core elements of Quality in Education. Learning outcome is considered as the core focus of quality in educational institutions. The Bloom’s (1958) provided learning classifications in three basic domains, i.e. Cognitive, Affective and Psychomotor. His work has provided the basic gadget for measuring and managing learning. This is used in developing academic standards, lesson plans, academic standards, exams, teaching methodologies, etc. They are discussed in detail with examples. The quality of learning can be framed against each of these levels. The importance of lesson plans (quality plans) is specially addressed.